Modification method of nano-cluster Y molecular sieve

Through the method of ion exchange and ammonium fluorosilicate treatment combined with hydrothermal dealuminum, the problem of skeleton collapse and degradation of properties in the traditional modification process of nanoclustered Y molecular sieve is solved, and the mesoporous content and stability are improved, and it is suitable for hydrogenation catalysts.

CN120515477APending Publication Date: 2025-08-22CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202410187134.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-20
Publication Date
2025-08-22

AI Technical Summary

Technical Problem

Nano-clustered Y molecular sieve is prone to problems such as collapse of the molecular sieve framework, a significant decrease in crystallinity, and a decrease in mesoporous content during the dealumination modification process of traditional acid and alkali treatment, which limits its industrial application prospects.

Method used

The sodium oxide content was controlled by ion exchange treatment to 2.0%-4.5%. The modified nanoclustered Y molecular sieve was prepared by shallow dealumination and siliconization by ammonium fluorosilicate solution, combined with hydrothermal dealumination and acid treatment.

Benefits of technology

The mesoporous content, hydrothermal stability and specific surface area of ​​the modified nanocluster Y molecular sieve is significantly improved, and the nanocluster morphology and high crystallinity are maintained, and it is suitable for hydrogenation catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120515477A_ABST
    Figure CN120515477A_ABST
Patent Text Reader

Abstract

The invention discloses a method for modifying a nano-cluster Y molecular sieve, which comprises the following steps of: (a) controlling the sodium oxide content of the nano-cluster Y molecular sieve to be 2.0-4.5% through ion exchange treatment; (b) adopting an ammonium fluosilicate solution to carry out shallow dealumination and silicon supplementation on the nano-cluster Y molecular sieve obtained in the step (a), wherein the shallow dealumination and silicon supplementation means that the silica-alumina ratio of the nano-cluster Y molecular sieve after dealumination and silicon supplementation is controlled to be increased by 50-200% compared with that of the nano-cluster Y molecular sieve before treatment, and preferably, the silica-alumina ratio of the nano-cluster Y molecular sieve after dealumination and silicon supplementation is increased by 80-150%; (c) carrying out hydrothermal dealumination treatment on the material obtained in the step (b); and (d) carrying out acid treatment on the material subjected to hydro-thermal treatment to obtain the modified nano-cluster Y molecular sieve. Compared with a nano-cluster Y molecular sieve before treatment, the modified Y molecular sieve prepared by adopting the modification method not only keeps the nano-cluster shape, but also greatly improves the mesoporous content and the hydrothermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a modification method of nano-clustered Y molecular sieve, in particular to a modification method for improving the physicochemical properties of the nano-clustered Y molecular sieve. Background Art

[0002] Molecular sieves, due to their unique structure and properties, are widely used in important fields such as catalysis and adsorption separation. Research on these materials has been ongoing for over half a century, with over 250 different topological molecular sieve types identified to date, and new molecular sieve structures are being developed annually. However, the small pores of most microporous molecular sieves can hinder molecular transport. For example, microporous Y molecular sieves can significantly restrict the mass transfer of large condensed aromatic hydrocarbons in the feedstock during petroleum cracking, leading to increased secondary reactions, poor product distribution, and pore blockage. Researchers generally believe that the preparation of microporous-mesoporous molecular sieves is an important approach to addressing the diffusion problem. Three main methods are commonly used to obtain hierarchically porous molecular sieves: post-processing of molecular sieves for pore formation, in-situ synthesis by adding sacrificial templates, and nanocrystal self-assembly of zeolite crystals. The first two methods have been the most studied, but they also present challenges such as molecular sieve framework collapse, decreased crystallinity, poor compatibility of the sacrificial template with the system, and high cost of the sacrificial template. In recent years, the preparation of hierarchically porous molecular sieve nanoclusters by nanocrystal self-assembly has garnered increasing attention. On the one hand, the "building block" of the cluster - the molecular sieve nanocrystals - has a smaller particle size, which can effectively shorten the diffusion path of the reaction molecules and reduce the diffusion resistance, while increasing the specific surface area and surface active sites of the molecular sieve and improving the accessibility of the active sites; on the other hand, the "cluster" configuration can effectively solve problems such as the difficulty of solid-liquid separation of molecular sieves caused by too small particle size.

[0003] CN108862309A provides a NaY molecular sieve aggregate with a nano-micro structure and a preparation method thereof, the method comprising the following steps: synthesizing a directing agent; preparing a reaction gel using the directing agent; and crystallizing the reaction gel to obtain a NaY molecular sieve aggregate with a nano-micro structure.

[0004] CN114074947A discloses a nanosheet Y molecular sieve aggregate and a preparation method and application thereof, comprising: mixing a silicon source, an aluminum source, an alkali solution and water in a molar ratio of (14-20) Na2O: (14-20) SiO2: Al2O3: (200-280) H2O, and aging the mixture at 5°C-60°C to obtain a directing agent; adding water, a silicon source, an aluminum source, an alkali source and the directing agent in a molar ratio of (0.5-2.5) Na2O: (5-7.5) SiO2: Al2O3: (100-200) H2O at 15°C-80°C to obtain a NaY reaction mixture; crystallizing the NaY reaction mixture at 80°C-140°C for 5h-100h, filtering, washing and drying the mixture to obtain the nanosheet Y molecular sieve aggregate.

[0005] CN1393402A discloses a method for preparing kaolin microsphere-supported nano-zeolite molecular sieve Y, comprising the following steps: 1) preparing a directing agent; 2) adding sodium citrate to the directing agent and magnetically stirring for 1.5-3 hours; the weight ratio of the directing agent to the sodium citrate being 65-75:2.5-3.5; 3) adding the calcined kaolin microspheres to the solution prepared in step 2) and mechanically stirring; the weight ratio of the added kaolin microspheres to the solution being 65-75:4-15; 4) dropwise adding sulfuric acid solution in an amount of 23%-32% of the weight of the solution prepared in step 3) and a concentration of 28%-32% to obtain a gel, which is shaken evenly and then crystallized at 90°C-110°C; and 5) separating the above product to obtain a kaolin microsphere-supported nano-zeolite molecular sieve Y product.

[0006] It is true that the micro-mesoporous channel structure of nano-clustered Y molecular sieve can effectively improve its mass transfer efficiency for large reactant molecules. However, it is well known that directly synthesized Y molecular sieve (including nano-clustered Y molecular sieve) is a non-acidic sodium-type molecular sieve and has a low silicon-aluminum ratio (usually SiO2 / Al2O3 molar ratio of 4-6). In the application process of petroleum cracking processing, it has shortcomings such as poor hydrothermal stability and short catalytic life. Generally, it needs to undergo dealumination modification such as acid treatment, alkali treatment or hydrothermal treatment before it can be used as an acidic support component of a cracking catalyst.

[0007] CN114713271A discloses a method for treating small-grain Y molecular sieves with a combination of weak base ammonia and organic small molecule bases. The prepared modified Y molecular sieve has a silicon-aluminum ratio of 8-60, a sodium oxide content of <0.1wt%, and a unit cell parameter of 2.433nm-2.452nm. However, this method has the problem that the crystallinity and specific surface area of ​​the Y molecular sieve are seriously reduced. The relative crystallinity of the modified Y molecular sieve is only 60%-90%, and the specific surface area of ​​the modified Y molecular sieve is 600m 2 / g-700m 2 / g, directly affects the catalytic effect of molecular sieve.

[0008] US5601798 reported a modification method of Y molecular sieve by hydrothermal treatment with ammonium nitrate or nitric acid solution in an autoclave. The silicon-aluminum ratio of the molecular sieve can be increased from the original 5.1 to 7.8 after modification, and the mesopore volume is also increased from the original 0.087 cm 3 / g increased to 0.2cm 3 / g, but the crystallinity of the molecular sieve has decreased significantly, from the original 96% to 70% or even lower.

[0009] It can be seen that Y molecular sieves with conventional particle sizes are prone to problems such as molecular sieve skeleton collapse, a sharp drop in crystallinity, and a sharp decrease in mesopore content during the traditional acid and alkali treatment dealumination modification process. Since the basic structural unit of the nano-clustered Y molecular sieve, the nano-Y crystal, has a smaller grain size and higher surface energy, it is foreseeable that the relevant physical properties of the nano-clustered Y molecular sieve will decrease more seriously after the traditional dealumination modification treatment, which greatly limits the industrial application prospects of the nano-clustered Y molecular sieve. Summary of the Invention

[0010] In view of the shortcomings of the existing technology, the present invention provides a modification method for nanoclustered Y molecular sieves. Compared with the nanoclustered Y molecular sieves before treatment, the modified Y molecular sieve prepared by this modification method not only maintains the nanocluster morphology, but also greatly improves the mesopore content and hydrothermal stability.

[0011] The present invention provides a method for modifying a nanoclustered Y molecular sieve, comprising the following steps:

[0012] (a) controlling the sodium oxide content of the nanoclustered Y molecular sieve to 2.0%-4.5% by ion exchange treatment;

[0013] (b) using an ammonium fluorosilicate solution to shallowly dealuminate and resiliconize the nanoclustered Y molecular sieve obtained in step (a), wherein the shallow dealuminate and resiliconize refers to controlling the silicon-aluminum ratio of the nanoclustered Y molecular sieve after dealuminate and resiliconization to be increased by 50%-200%, preferably by 80%-150%, compared with the nanoclustered Y molecular sieve before treatment;

[0014] (c) subjecting the material obtained in step (b) to a hydrothermal dealumination treatment;

[0015] (d) The material after hydrothermal treatment is subjected to acid treatment to obtain modified nano-clustered Y molecular sieve.

[0016] In the method of the present invention, the nano-clustered Y molecular sieve can be prepared according to existing public technology or using commercially available products.

[0017] In the method of the present invention, the average particle size of the nano-clustered Y molecular sieve is 1 μm-5 μm, preferably 1.5 μm-2 μm. The average particle size of the nanoparticles constituting the nano-clustered Y molecular sieve clusters is about 5 nm-100 nm, preferably 40 nm-70 nm.

[0018] In the method of the present invention, the total pore volume of the nano-clustered Y molecular sieve is 0.3 cm 3 / g-0.6cm 3 / g, preferably 0.35cm 3 / g-0.45cm 3 / g; specific surface area is 600m 2 / g-900m 2 / g, preferably 700m 2 / g-800m 2 / g.

[0019] In the method of the present invention, the nano-clustered Y molecular sieve has a typical FAU-type topological structure; the silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of the nano-clustered Y molecular sieve is 4.5-6.0, preferably 5.0-5.5.

[0020] In the method of the present invention, the nano-clustered Y molecular sieve is one of Na-type nano-clustered Y molecular sieve, ammonium-type nano-clustered Y molecular sieve or hydrogen-type nano-clustered Y molecular sieve.

[0021] In the method of the present invention, the specific process of the ion exchange in step (a) is as follows: the nanoclustered Y molecular sieve is subjected to ion exchange with a salt solution at 30-120° C., preferably 60-90° C., for 1-3 hours, and the number of exchanges is 1-3 times.

[0022] In the method of the present invention, the salt used in the ion exchange in step (a) is one or more of ammonium chloride, ammonium nitrate, ammonium sulfate, ammonium acetate, ammonium oxalate, sodium chloride and sodium nitrate, and the concentration of the salt solution is 0.5 mol / L-3 mol / L, preferably 1 mol / L-2 mol / L. The solid-to-liquid ratio of the nanoclustered Y molecular sieve to the salt solution is 1:5-15 (g:mL), preferably 1:8-10 (g:mL).

[0023] In the method of the present invention, step (a) controls the nanoclustered Y molecular sieve to contain an appropriate amount of sodium ions. Based on the weight of the nanoclustered Y molecular sieve, the mass content of sodium ions calculated as sodium oxide is 2.0%-4.5%, preferably 2.5%-4.0%.

[0024] In the method of the present invention, the nanoclustered Y molecular sieve is controlled to contain an appropriate amount of sodium ions, which can be obtained by ammonium exchange or sodium ion exchange, that is, for a high sodium ion content, the sodium ion content is reduced by ammonium exchange, and for a low sodium ion content, an appropriate amount of sodium is added.

[0025] The results show that an appropriate amount of Na ions in the ammonium fluorosilicate solution-modified nanoclustered Y molecular sieves balances the framework charge and stabilizes the sodalite cages. The lower-energy Al-O bonds in the framework are preferentially broken or semi-broken, causing some sodalite cages to distort and break, while others remain stable due to the presence of Na ions. Ultimately, dealumination allows for the formation of a certain amount of secondary mesopores while maintaining a high degree of crystallinity. Therefore, retaining an appropriate amount of Na ions in the nanoclustered Y molecular sieves is crucial for improving the framework stability during the dealumination process.

[0026] In the method of the present invention, in step (b), the nano-clustered Y molecular sieve is treated with an ammonium fluorosilicate solution at 60°C-120°C, preferably 80°C-100°C, for 3h-5h, and the treatment times are 1-2 times to obtain the pretreated Y molecular sieve.

[0027] In the method of the present invention, the concentration of the ammonium fluorosilicate solution in step (b) is 0.02 mol / L-0.15 mol / L.

[0028] In the method of the present invention, the solid-to-liquid ratio of the nano-clustered Y molecular sieve to the ammonium fluorosilicate solution in step (b) is 1:20-50 (g:mL).

[0029] In the method of the present invention, the hydrothermal treatment in step (c) is a steam heat treatment: the material obtained in step (b) is contacted with steam at a temperature of 500-700°C and a pressure of 0.01-0.5 MPa for 1-4 hours. Preferably, the steam heat treatment is performed 1-2 times.

[0030] In the method of the present invention, the acid treatment process in step (d) is to treat the material after the hydrothermal treatment in step (c) with an acid solution at a constant temperature of 50-120° C. for 1-3 hours.

[0031] In the method of the present invention, the acid in step (d) is one or more of nitric acid, sulfuric acid, hydrochloric acid, citric acid and oxalic acid, and the concentration of the acid solution is 0.2-1.5 mol / L, preferably 0.5-1.0 mol / L.

[0032] In the method of the present invention, in step (d), the solid-to-liquid ratio of the material after the hydrothermal treatment in step (c) to the acid solution is 1:6-15 (g:mL), preferably 1:8-10 (g:mL).

[0033] The modified nano-clustered Y molecular sieve product obtained by the modification method of the present invention has the following properties: the modified nano-clustered Y molecular sieve still maintains a clear nano-cluster morphology; the average particle size of the modified molecular sieve clusters is 1μm-5μm, preferably 1.5μm-2μm. The average particle size of the nanoparticles constituting the modified nano-clustered Y molecular sieve clusters is about 5nm-100nm, preferably 40nm-70nm. The total pore volume of the modified nano-clustered Y molecular sieve is 0.4cm 3 / g-0.7cm 3 / g, preferably 0.45cm 3 / g-0.6cm 3 / g, the mesopore volume accounts for 30%-55% of the total pore volume, preferably 35%-50%, and the specific surface area is 600m 2 / g-900m 2 / g, preferably 650m 2 / g-750m 2 / g; the modified nanocluster Y molecular sieve has a typical FAU type topology. The nanocluster Y molecular sieve before modification is used as a standard sample, and the relative crystallinity of the modified nanocluster Y molecular sieve is 90%-110%; the silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of the modified nanocluster Y molecular sieve is 8-50, preferably 10-30.

[0034] Application of the modified nanoclustered Y molecular sieve in the preparation of hydrogenation catalysts.

[0035] As is known to all, the physicochemical stability of nano-clustered Y-type molecular sieves is poor, and the existing molecular sieve modification methods for nano-clustered Y-type molecular sieves often cause the structure and physicochemical properties of nano-clustered Y-type molecular sieves to be destroyed and / or the physicochemical properties to deteriorate. The method of the present invention first utilizes the stabilizing effect of sodium ions on the sodalite cages in the molecular sieve framework, and appropriately controls the sodium oxide content in the nano-clustered Y-type molecular sieve to improve the stability of the molecular sieve framework in the subsequent dealumination process; then, the nano-clustered Y-type molecular sieve is shallowly dealuminated and siliconized by an ammonium fluorosilicate solution, with the change of the silicon-aluminum ratio before and after as the main control index, and the shallow dealuminated siliconizing process makes the nano-clustered Y-type molecular sieve easily contacted with the ammonium fluorosilicate for dealuminated siliconizing, thereby pre-stabilizing the main structure of the nano-clustered Y-type molecular sieve, and finally, hydrothermal dealuminating is mainly performed on the inside of the nano-clustered Y-type molecular sieve through a hydrothermal treatment process. The realization of the above-mentioned inventive concept significantly improves the properties of the modified nano-clustered Y-type molecular sieve in various aspects, especially in terms of pore structure and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the SEM photo of the nanoclustered Y molecular sieve in Example 1 of the present invention.

[0037] Figure 2 This is the SEM photo of the modified nanoclustered Y molecular sieve in Example 1 of the present invention.

[0038] Figure 3 This is the SEM photo of the nanoclustered Y molecular sieve in Example 4 of the present invention.

[0039] Figure 4 This is the SEM photo of the modified nanoclustered Y molecular sieve in Example 4 of the present invention.

[0040] Figure 5 This is the SEM photo of the nanoclustered Y molecular sieve in Example 5 of the present invention.

[0041] Figure 6 This is the SEM photo of the modified nanoclustered Y molecular sieve in Example 5 of the present invention. DETAILED DESCRIPTION

[0042] The present invention is described in further detail below in conjunction with specific examples. The examples are implemented under the premise of the technical solution of the present invention, and detailed implementation methods and specific operating procedures are provided, but the protection scope of the present invention is not limited to the following examples. The experimental methods in the following examples, unless otherwise specified, are conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, were purchased from conventional biochemical reagent stores.

[0043] In the present invention, the morphology of the synthesized molecular sieve is determined by SEM; the average particle size of the molecular sieve is determined by a laser particle size analyzer, and the average particle size of the nanocrystals constituting the clusters is determined by the empirical formula d=4061 / S ext Determine (where d is the particle size in nm, S exteral is the external specific surface area of ​​the cluster, in m 2 / g); the crystal structure and relative crystallinity of the molecular sieve were determined by XRD characterization; the elemental composition of the molecular sieve was determined by XRF characterization; and the pore information was obtained by nitrogen adsorption-desorption testing of the molecular sieve using an ASAP 2420 automatic physical adsorption instrument at 77K.

[0044] Example 1

[0045] (1) Nanoclustered Y molecular sieves were prepared using the method described in Example 1 of CN108862309A, such as Figure 1 As shown (the average particle size of the nanocluster Y molecular sieve is 3.4 μm; the average size of the nanocrystals constituting the nanocluster Y molecular sieve is 52 nm; the specific surface area is 708 m 2 / g, with a total pore volume of 0.42 cm 3 / g, of which the mesopore volume accounts for 23.5% of the total pore volume; the silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of the nanocluster Y molecular sieve is 5.2; the Na2O mass content in the nanocluster Y molecular sieve is 12.0%), the nanocluster Y molecular sieve is mixed with a 1.0 mol / L ammonium nitrate solution at a solid-liquid ratio of 1:10, and ammonium ion exchange is carried out at 80°C for 2h to obtain a nanocluster Y molecular sieve with a Na2O mass content of 4.0%.

[0046] (2) The nanoclustered Y molecular sieve obtained in step (1) was mixed with a 0.05 mol / L ammonium fluorosilicate solution at a solid-liquid ratio of 1:30, and treated at 90°C for 4 hours to obtain a pretreated Y molecular sieve having a silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of 10.5, which was 102% higher than that of the nanoclustered Y molecular sieve before treatment.

[0047] (3) The pretreated Y molecular sieve was contacted with water vapor at a temperature of 600°C and a pressure of 0.1 MPa for 2 h to obtain a dealuminated Y molecular sieve.

[0048] (4) The dealuminated Y molecular sieve was mixed with a 0.5 mol / L nitric acid solution at a solid-liquid ratio of 1:10 and treated at 80°C for 2 hours to obtain a modified nanoclustered Y molecular sieve. The modified nanoclustered Y molecular sieve retained a distinct nanocluster morphology ( Figure 2 ), the average particle size is still 3.4 μm, and the average size of the nanocrystals constituting the nanoclustered Y molecular sieve is 52 nm; the total pore volume of the modified nanoclustered Y molecular sieve is 0.51 cm 3 / g, the mesopore volume accounts for 42.2% of the total pore volume, and the specific surface area is 660m 2 / g; the modified nanocluster Y molecular sieve has a typical FAU-type topology. Taking the nanocluster Y molecular sieve as a standard sample, the modified nanocluster Y molecular sieve has a relative crystallinity of 98%; the silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of the modified nanocluster Y molecular sieve is 16.8.

[0049] Example 2

[0050] Step (1) is the same as in Example 1.

[0051] (2) The nanoclustered Y molecular sieve obtained in step (1) was mixed with a 0.02 mol / L ammonium fluorosilicate solution at a solid-liquid ratio of 1:20, and treated at 60°C for 3 hours to obtain a pretreated Y molecular sieve having a silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of 8.2, which was 57.7% higher than that of the nanoclustered Y molecular sieve before treatment.

[0052] Steps (3)-(4) are the same as those in Example 1. The properties of the modified nanoclustered Y molecular sieve obtained are as follows: the modified nanoclustered Y molecular sieve retains a distinct nanocluster morphology, its average particle size is still 3.4 μm, and the average size of the nanocrystals constituting the nanoclustered Y molecular sieve is 52 nm; the total pore volume of the modified nanoclustered Y molecular sieve is 0.47 cm 3 / g, the mesopore volume accounts for 38.2% of the total pore volume, and the specific surface area is 695m 2 / g; the modified nanocluster Y molecular sieve has a typical FAU-type topology. The nanocluster Y molecular sieve before modification is used as a standard sample. The relative crystallinity of the modified nanocluster Y molecular sieve is 102%; the silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of the modified nanocluster Y molecular sieve is 12.7.

[0053] Example 3

[0054] Step (1) is the same as in Example 1.

[0055] (2) The nanoclustered Y molecular sieve obtained in step (1) was mixed with a 0.1 mol / L ammonium fluorosilicate solution at a solid-liquid ratio of 1:50, and treated at 120°C for 3 hours to obtain a pretreated Y molecular sieve having a silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of 14.6, which was 180% higher than that of the nanoclustered Y molecular sieve before treatment.

[0056] Steps (3)-(4) are the same as those in Example 1. The properties of the modified nanoclustered Y molecular sieve obtained are as follows: the modified nanoclustered Y molecular sieve retains a distinct nanocluster morphology, its average particle size is still 3.4 μm, and the average size of the nanocrystals constituting the nanoclustered Y molecular sieve is 52 nm; the total pore volume of the modified nanoclustered Y molecular sieve is 0.62 cm 3 / g, the mesopore volume accounts for 44.7% of the total pore volume, and the specific surface area is 617m 2 / g; the modified nanocluster Y molecular sieve has a typical FAU-type topology. The nanocluster Y molecular sieve before modification is used as a standard sample, and the relative crystallinity of the modified nanocluster Y molecular sieve is 92%; the silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of the modified nanocluster Y molecular sieve is 32.8.

[0057] Example 4

[0058] (1) Nanoclustered Y molecular sieves were prepared by the method described in Example 1 of CN114074947A. Figure 3 The average particle size of the nanoclustered Y molecular sieve is 4.0 μm; the average size of the nanocrystals constituting the nanoclustered Y molecular sieve is 78 nm; the specific surface area is 725 m 2 / g, with a total pore volume of 0.38 cm3 / g, of which the mesopore volume accounts for 18.4% of the total pore volume; the silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of the nanoclustered Y molecular sieve is 5.4; the Na2O mass content in the nanoclustered Y molecular sieve is 11.3%), the nanoclustered Y molecular sieve is mixed with a 1.0 mol / L ammonium nitrate solution at a solid-liquid ratio of 1:10, and ammonium ion exchange is carried out at 80°C for 2h. The process is repeated once to obtain a nanoclustered Y molecular sieve with a Na2O mass content of 3.2%.

[0059] (2) The nanoclustered Y molecular sieve obtained in step (1) was mixed with a 0.12 mol / L ammonium fluorosilicate solution at a solid-liquid ratio of 1:30, and treated at 100°C for 3 hours to obtain a pretreated Y molecular sieve having a silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of 13.6, which was 152% higher than that of the nanoclustered Y molecular sieve before treatment.

[0060] (3) The pretreated Y molecular sieve was contacted with water vapor at a temperature of 700°C and a pressure of 0.2 MPa for 1 hour to obtain a dealuminated Y molecular sieve.

[0061] (4) The dealuminated Y molecular sieve was mixed with a 1 mol / L nitric acid solution at a solid-liquid ratio of 1:10 and treated at 60°C for 2 h to obtain a modified nanoclustered Y molecular sieve. The modified nanoclustered Y molecular sieve retained a distinct nanocluster morphology ( Figure 4 ), the average particle size is still 4.0 μm, and the average size of the nanocrystals constituting the nanoclustered Y molecular sieve is 78 nm; the total pore volume of the modified nanoclustered Y molecular sieve is 0.57 cm 3 / g, the mesopore volume accounts for 43.5% of the total pore volume, and the specific surface area is 700m 2 / g; the modified nanocluster Y molecular sieve has a typical FAU type topology. Taking the nanocluster Y molecular sieve as a standard sample, the modified nanocluster Y molecular sieve has a relative crystallinity of 95%; the silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of the modified nanocluster Y molecular sieve is 27.8.

[0062] Example 5

[0063] (1) The commercially available hydrogen nanoclustered Y molecular sieve (see Figure 5 The average particle size of the nanocluster Y molecular sieve is 2.4 μm; the average size of the nanocrystals that make up the nanocluster Y molecular sieve is 65 nm; the specific surface area is 855 m 2 / g, with a total pore volume of 0.39 cm 3 / g, of which the mesopore volume accounts for 20.6% of the total pore volume; the silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of the nanocluster Y molecular sieve is 5.1; the nanocluster Y molecular sieve (Na2O content by mass 0.3%) is mixed with a 0.5 mol / L sodium nitrate solution at a solid-liquid ratio of 1:10 and treated at 60°C for 1 hour to obtain a nanocluster Y molecular sieve with a Na2O content of 4.5%.

[0064] (2) The nanoclustered Y molecular sieve obtained in step (1) was mixed with a 0.03 mol / L ammonium fluorosilicate solution at a solid-liquid ratio of 1:20, treated at 60°C for 5 hours, and then the operation was repeated once to obtain a pretreated Y molecular sieve having a silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of 11.9, which was 133% higher than that of the nanoclustered Y molecular sieve before treatment.

[0065] (3) The pretreated Y molecular sieve was contacted with water vapor at a temperature of 550°C and a pressure of 0.05 MPa for 1 hour to obtain a dealuminated Y molecular sieve.

[0066] (4) The dealuminated Y molecular sieve was mixed with a 1 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:10 and treated at 80°C for 2 hours to obtain a modified nanoclustered Y molecular sieve. The modified nanoclustered Y molecular sieve retained a distinct nanocluster morphology ( Figure 6 ), the average particle size is still 2.4 μm, and the average size of the nanocrystals constituting the nanoclustered Y molecular sieve is 65 nm; the total pore volume of the modified nanoclustered Y molecular sieve is 0.48 cm 3 / g, the mesopore volume accounts for 41.0% of the total pore volume, and the specific surface area is 820m 2 / g; the modified nanocluster Y molecular sieve has a typical FAU-type topology. The nanocluster Y molecular sieve before modification is used as a standard sample, and the relative crystallinity of the modified nanocluster Y molecular sieve is 105%; the silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of the modified nanocluster Y molecular sieve is 18.9.

[0067] Comparative Example 1

[0068] The modification process of the nanoclustered Y molecular sieve is the same as that of Example 1, except that step (2), i.e., the pretreatment process of the nanoclustered Y molecular sieve with ammonium fluorosilicate solution, is omitted. The properties of the modified nanoclustered Y molecular sieve obtained after the subsequent experimental steps are as follows: the modified nanoclustered Y molecular sieve clusters still maintain a clear nanocluster morphology; however, the total pore volume of the modified nanoclustered Y molecular sieve is only 0.37 cm 3 / g, the mesopore volume accounts for 27.5% of the total pore volume, and the specific surface area is 570m 2 / g; the modified nanoclustered Y molecular sieve has a typical FAU-type topology. Taking the unmodified nanoclustered Y molecular sieve as a standard sample, the modified nanoclustered Y molecular sieve has a relative crystallinity of 72%; the modified nanoclustered Y molecular sieve has a silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of 10.4. It can be seen that when the nanoclustered Y molecular sieve is directly hydrothermally dealuminated, on the one hand, the degree of dealumination of the molecular sieve is low, resulting in a low silicon-to-aluminum ratio of the modified molecular sieve product. On the other hand, due to the small particle size and high surface energy of the nanoparticles, the direct hydrothermal treatment causes partial collapse of the molecular sieve framework, resulting in a significant decrease in the specific surface area, number of mesopores, and crystallinity of the resulting modified nanoclustered Y molecular sieve.

[0069] Comparative Example 2

[0070] The modification process of the nanoclustered Y molecular sieve was the same as in Example 4, except that the Si / Al ratio of the pretreated molecular sieve was controlled to 26.6, which was 412% higher than that of the pretreated nanoclustered Y molecular sieve. The properties of the modified nanoclustered Y molecular sieve obtained through subsequent experimental steps were as follows: the modified nanoclustered Y molecular sieve clusters still maintained a distinct nanocluster morphology; however, the total pore volume of the modified nanoclustered Y molecular sieve was 0.24 cm 3 / g, the mesopore volume accounts for 11.5% of the total pore volume, and the specific surface area is 509m 2 / g; the modified nanoclustered Y molecular sieve has a typical FAU-type topology. Using the unmodified nanoclustered Y molecular sieve as a standard sample, the modified nanoclustered Y molecular sieve has a relative crystallinity of 44%; and the modified nanoclustered Y molecular sieve has a silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of 65.4. It can be seen that when the nanoclustered Y molecular sieve is deeply dealuminated and siliconized using an ammonium fluorosilicate solution, a large number of Al-O bonds are broken, causing a large number of sodalite cages in the molecular sieve framework to distort and damage. Further hydrothermal dealumination ultimately causes severe collapse of the molecular sieve framework, resulting in a significant reduction in the specific surface area, number of mesopores, and crystallinity of the modified nanoclustered Y molecular sieve.

[0071] Comparative Example 3

[0072] The modification process of the nanoclustered Y molecular sieve is the same as that of Example 5, except that step (1), i.e., the ion exchange process of the hydrogen-type nanoclustered Y molecular sieve, is omitted. The properties of the modified nanoclustered Y molecular sieve finally obtained after the subsequent experimental steps are as follows: the modified nanoclustered Y molecular sieve clusters still maintain a clear nanocluster morphology; however, the total pore volume of the modified nanoclustered Y molecular sieve is 0.33 cm 3 / g, the mesopore volume accounts for 33.5% of the total pore volume, and the specific surface area is 609m 2 / g; the modified nanoclustered Y molecular sieve has a typical FAU-type topology. Taking the unmodified nanoclustered Y molecular sieve as a standard sample, the modified nanoclustered Y molecular sieve has a relative crystallinity of 70%; the modified nanoclustered Y molecular sieve has a silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of 22.4. It can be seen that when the sodium oxide content in the nanoclustered Y molecular sieve is low, due to the lack of sodium ions on the stability of the Y molecular sieve framework, the nanoclustered Y molecular sieve will also experience obvious skeleton collapse during the subsequent ammonium fluorosilicate treatment and hydrothermal dealumination and siliconization process, resulting in a decrease in the crystallinity, specific surface area, and mesopore content of the final modified nanoclustered Y molecular sieve product.

[0073] Comparative Example 4

[0074] The modification process of the nanoclustered Y molecular sieve was the same as in Example 4, except that the Si / Al ratio of the pretreated molecular sieve was controlled to 7.0, which was 30% higher than that of the pretreated nanoclustered Y molecular sieve. The properties of the modified nanoclustered Y molecular sieve obtained through subsequent experimental steps were as follows: the modified nanoclustered Y molecular sieve clusters still maintained a distinct nanocluster morphology; however, the total pore volume of the modified nanoclustered Y molecular sieve was only 0.35 cm 3 / g, the mesopore volume accounts for 37.2% of the total pore volume, and the specific surface area is 513m 2 / g; the modified nanoclustered Y molecular sieve has a typical FAU-type topology. Taking the unmodified nanoclustered Y molecular sieve as a standard sample, the modified nanoclustered Y molecular sieve has a relative crystallinity of 66%; the silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of the modified nanoclustered Y molecular sieve is 14.8. It can be seen that when the nanoclustered Y molecular sieve is pretreated with ammonium fluorosilicate at a shallow level, the stabilization degree of the molecular sieve framework is low, resulting in partial collapse of the molecular sieve framework during subsequent hydrothermal treatment, and the specific surface area, number of mesopores, and crystallinity of the obtained modified nanoclustered Y molecular sieve are significantly reduced.

[0075] By comparing the characterization data of the modified nano-clustered Y molecular sieves in the examples and the comparative examples, it can be seen that the poor stability of the nano-molecular sieve leads to easy skeleton collapse during its modification process, and the modified molecular sieve specific surface area, pore volume, mesopore volume and relative crystallinity and other indicators decrease. The modification method of the nano-clustered Y molecular sieve provided by the present invention can effectively improve the skeleton strength of the nano-clustered Y molecular sieve during the molecular sieve dealumination modification process by accurately controlling the sodium oxide content in the molecular sieve and the degree of dealumination of the molecular sieve during the ammonium fluorosilicate pretreatment, and ultimately achieve the purpose of improving key application indicators such as the modified specific surface area, molecular sieve mesopore volume and crystallinity.

Claims

1. A method for modifying nanoclustered Y molecular sieves, characterized by: Includes the following: (a) controlling the sodium oxide content of the nanoclustered Y molecular sieve to 2.0%-4.5% by ion exchange treatment; (b) using an ammonium fluorosilicate solution to shallowly dealuminate and resiliconize the nanoclustered Y molecular sieve obtained in step (a), wherein the shallow dealuminate and resiliconize refers to controlling the silicon-aluminum ratio of the nanoclustered Y molecular sieve after dealuminate and resiliconization to be increased by 50%-200%, preferably by 80%-150%, compared with the nanoclustered Y molecular sieve before treatment; (c) subjecting the material obtained in step (b) to a hydrothermal dealumination treatment; (d) The material after hydrothermal treatment is subjected to acid treatment to obtain modified nano-clustered Y molecular sieve.

2. The method according to claim 1, wherein: The average particle size of the nano-clustered Y molecular sieve is 1 μm-5 μm, preferably 1.5 μm-2 μm.

3. The method according to claim 1, wherein: The average particle size of the nanoparticles constituting the nanoclustered Y molecular sieve clusters is about 5nm-100nm, preferably 40nm-70nm.

4. The method according to claim 1, wherein: The total pore volume of the nano-clustered Y molecular sieve is 0.3 cm 3 / g-0.6cm 3 / g, preferably 0.35cm 3 / g-0.45cm 3 / g; specific surface area is 600m 2 / g-900m 2 / g, preferably 700m 2 / g-800m 2 / g.

5. The method according to claim 1, wherein: The nano-clustered Y molecular sieve has a typical FAU topological structure; the SiO2 / Al2O3 molar ratio of the nano-clustered Y molecular sieve is 4.5-6.0, preferably 5.0-5.

5.

6. The method according to claim 1, wherein: The nano-clustered Y molecular sieve is one of a Na-type nano-clustered Y molecular sieve, an ammonium-type nano-clustered Y molecular sieve or a hydrogen-type nano-clustered Y molecular sieve.

7. The method according to claim 1, wherein: The specific process of the ion exchange in step (a) is as follows: the nano-clustered Y molecular sieve is subjected to ion exchange with a salt solution at 30-120° C., preferably 60-90° C., for 1-3 hours, and the number of exchanges is 1-3 times.

8. The method according to claim 1, wherein: The salt used in the ion exchange in step (a) is one or more of ammonium chloride, ammonium nitrate, ammonium sulfate, ammonium acetate, ammonium oxalate, sodium chloride and sodium nitrate, the concentration of the salt solution is 0.5 mol / L-3 mol / L, preferably 1 mol / L-2 mol / L, and the solid-liquid ratio of the nanoclustered Y molecular sieve to the salt solution is 1:5-15 (g:mL), preferably 1:8-10 (g:mL).

9. The method according to claim 1, wherein: In step (a), the nano-clustered Y molecular sieve contains an appropriate amount of sodium ions, wherein the mass content of the sodium ions calculated as sodium oxide is 2.5%-4.0% based on the weight of the nano-clustered Y molecular sieve.

10. The method according to claim 1, wherein: In step (b), the nano-clustered Y molecular sieve is treated with the ammonium fluorosilicate solution at 60° C.-120° C., preferably 80° C.-100° C., for 3 h-5 h, and the treatment frequency is 1-2 times.

11. The method according to claim 1, wherein: The concentration of the ammonium fluorosilicate solution described in step (b) is 0.02mol / L-0.15mol / L.

12. The method according to claim 1, wherein: The solid-to-liquid ratio of the nano-clustered Y molecular sieve to the ammonium fluorosilicate solution in step (b) is 1:20-50 (g:mL).

13. The method according to claim 1, wherein: The hydrothermal treatment in step (c) is steam heat treatment: the material obtained in step (b) is contacted with steam at a temperature of 500-700°C and a pressure of 0.01-0.5 MPa for 1-4 hours. Preferably, the steam heat treatment is performed 1-2 times.

14. The method according to claim 1, wherein: The acid treatment process in step (d) is to treat the material after the hydrothermal treatment in step (c) with an acid solution at a constant temperature of 50-120° C. for 1-3 hours.

15. The method according to claim 1, wherein: The acid in step (d) is one or more of nitric acid, sulfuric acid, hydrochloric acid, citric acid and oxalic acid, and the concentration of the acid solution is 0.2-1.5 mol / L, preferably 0.5-1.0 mol / L.

16. The method according to claim 1, wherein: In step (d), the solid-to-liquid ratio of the material after the hydrothermal treatment in step (c) to the acid solution is 1:6-15 (g:mL), preferably 1:8-10 (g:mL).

17. A modified nano-clustered Y molecular sieve prepared by the method according to any one of claims 1 to 16.

18. Use of the modified nanoclustered Y molecular sieve according to claim 17 in the preparation of a hydrogenation catalyst.

Citation Information

Patent Citations

  • NaY molecular sieve aggregate with nano-micro structure and preparation method thereof

    CN108862309A

  • Nano sheet Y molecular sieve aggregate as well as preparation method and application thereof

    CN114074947A

  • Process for preparing nano Y zeolite molecular sieve carried by kaolin microspheres

    CN1393402A

  • Process for preparing zeolite Y with increased mesopore volume

    US5601798A

Cited By

  • Modification method of molecular sieve topological structure

    CN121588762A